The Influence of Digital Marketing and E-WOM on Interest in Visiting Atlantis Land - Ralfael Al Hafizh Ferdiansyah; Ugy Soebiantoro (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of Digital Marketing on Interest in Visiting Atlantis Land East Surabaya and the effect of E-WOM on Interest in Visiting Atlantis Land Surabaya. The population in this study are visitors to Atlantis Land who are over 18 years old. The sample in this study used the Ghozali formula and found 112 respondents. The method used in this study uses the GForm form. The analysis technique in this study uses PLS (Partial Least Square). The results of this study indicate that the Digital Marketing indicator variable that has the highest percentage is video content that displays all the attractions and rides of Atlantis Land Surabaya which are very interesting (X1).